A treatise on Organophosphate pesticide pollution: Current strategies and advancements in their environmental degradation and elimination - Kaushal, Jyoti; Khatri, Madhu; Arya, Shailendra Kumar (Ecotoxicology and environmental safety, 2021)
Pesticides have been used in the field of agriculture ever since their role in protection of crops from pests which include four different categories namely insects, mites, rodents and animals has been identified. Organophosphate pesticides are one of the most extensively applied insecticides in the field of agriculture such that around 40% of all the pesticides that are produced and used commercially belong to this category. The main toxicological effect of these pesticides when exposed to a living being encompasses the irremediable inhibition of the acetylcholinesterase (AChE) enzyme which is involved in the neurotransmission of signals and hence its inhibition causes impairment of the respiratory tract and neuromuscular transmission. Apart from being used as a pesticide, organophosphates have also been applied as herbicides to some extent. The residues of these highly toxic chemicals have found route into the underground water system by seeping into the ground, in rivers where the agricultural run off water is disposed, and in the air when sprayed on the crops hence posing a threat to all the living strata exposed to these chemicals in various ways which are discussed further. Many significant studies have been carried out in order to evaluate the health risks associated with these pesticides which commonly include acute neurological disorders. This review emphasizes on the toxicological effects of organophosphate pesticides and the recent methods of detection that are used to identify trace amounts of organophosphate pesticides along with strategies which are used for their degradation. •Organophosphate pesticides have been identified as inhibitory substances for enzyme Acetylcholinesterase.•The blockage of the enzyme’s active site by organophosphate phosphorylation reaction occurs at serine residue.•The detection strategies for organophosphate pesticides are described which include many biological, chemical and physical parameters.•Degradation strategies, both biotic and abiotic for organophosphate pesticide degradation are discussed.